A Man and His Minnows: The Introduction of Gambusia affinis to Mandatory Palestine - Kulman, Alina; Tamïr, Dan (Frontiers in Conservation Science, 2022)
While the ecological aspects of aquatic introductions are thoroughly researched, lesser attention has been given to the social, historical, cultural, and ideological contexts of such intended introductions. The introduction of Gambusia affinis to Palestine was made quickly by one person, who documented the process – and hence may serve as an excellent case study: Israel Kligler’s scientific reports and personal correspondence from the late 1920s and early 1930s provide us with an opportunity to witness the thoughts and ideas behind that introduction process. We find that the swift and quick introduction was facilitated by a combination of three factors: Zionist institutions’ desire to test new scientific tools and methods, the British colonial desire to control the environment and actively “ameliorate” it, and Kligler’s close working ties with US-American institutions. We argue that histories of introductions should be regarded and analyzed by examining such technical-political conjunctures.